The Malay version of the caregiver assessment of function and upset instrument (Malay-CAFU): a translation and validation study among informal stroke caregivers - Nurfaten Hamzah; Kamarul Imran Musa; Muhammad Hibatullah Romli; Xin Wee Chen; Mohd Zulkifli Abdul Rahim; Jafri Malin Abdullah; Mohd Azmi Suliman; Mohd Ismail Ibrahim; Tengku Alina Tengku Ismail; Iliatha Papachristou Nadal; Suresh Kumar Kamalakannan (BMC, 2023)
Abstract Background Post-stroke complications affect the informal caregivers equally as the stroke survivors, especially those who have a moderate to worst prognosis in functional capacity recovery. Caregiver Assessment of Function and Upset (CAFU) is one of the common tools used in both research and clinical practice to measure the patient's dependency level and the stroke caregivers' upset level. Objective This study aimed to translate and validate the CAFU instrument into the Malay language and test the validity and reliability of the CAFU among informal stroke caregivers in Malaysia. Methods A standard forward-backward translation method was employed to translate CAFU. Subsequently, 10 expert panels were included in the validation process, and thereafter reliability testing was conducted among 51 stroke caregivers. The validation of the instrument was determined by computing the content validity indices (CVIs), and we used the Cronbach's alpha method to explore the internal consistency of the overall score and subscales scores of the Malay-CAFU. Finally, the explanatory factor analysis used principal component extraction and a varimax rotation to examine construct validity. Results All items of the Malay-CAFU had satisfactory item-level CVI (I-CVI), with values greater than 0.80, and the scale-level CVI (S-CVI) was 0.95. These results indicate that the Malay-CAFU had good relevancy. The internal consistency for the reliability test showed a Cronbach's alpha value of 0.95 for the overall score. The eigenvalues and scree plot supported a two-factor structural model of the instrument. From the explanatory factor analysis, the factor loadings ranged from 0.82 to 0.90 and 0.56 to 0.83, respectively. Conclusion The Malay-CAFU questionnaire is a valid and reliable instrument to assess the dependence level of stroke survivors and the upset level of informal stroke caregivers in Malaysia.